"Land belongs to the people of Uganda": politicians' use of land issues in the 2016 election campaigns. Issue 4 (1st October 2016) - Meinert, Lotte; Kjær, Anne Mette
ABSTRACT: Politicians running for the 2016 elections in Uganda used land issues in various ways to mobilize votes. We explore the ways in which land was politicized during election campaigns, by examining the personal manifestos and rallies of candidates in the districts of Kaabong and Gulu, and in Kampala. Our main argument is that land was often constitutive of programmatic political debate, and was not only used in instrumental and patrimonial ways to mobilize votes. The most significant ways in which land was used in the election were to: raise questions of authorities' and investors' claims and "land-grabbing"; start discussions about land development, sale, and forms of tenure; buy votes with land (promises or access); encourage squatting on investors' land to create conflicts over claims and gain popularity, and thus, votes; and raise issues about ethnicity, territorial rights, and autochthony.